2021
DOI: 10.3389/fgene.2021.638555
|View full text |Cite
|
Sign up to set email alerts
|

Univariate and Multivariate QTL Analyses Reveal Covariance Among Mineral Elements in the Rice Ionome

Abstract: Rice provides more than one fifth of daily calories for half of the world’s human population, and is a major dietary source of both essential mineral nutrients and toxic elements. Rice grains are generally poor in some essential nutrients but may contain unsafe levels of some toxic elements under certain conditions. Identification of quantitative trait loci (QTLs) controlling the concentrations of mineral nutrients and toxic trace metals (the ionome) in rice will facilitate development of nutritionally improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The most commonly identified StHD QTL was qStHD8-2, which co-located with QTL previously identified in four different populations (Pan et al, 2012;Li et al, 2016;Murugaiyan et al, 2019). When the RMC QTL for grain-As were compared with previously reported As QTL determined in various biparental mapping or GWA populations (Zhang et al, 2008;Norton et al, 2012a;Norton et al, 2014;Zhang et al, 2014;Norton et al, 2019;Liu et al, 2021), nine of the 15 RMC grain-As GWA-QTL coincided with a previously reported grain-As locus (Table 4). Four of the 11 RMC QTL for P, six of 18 for S, one of 19 for Ca, and 2 of 9 for Cu were validated by known transporter genes or previous QTL studies (Zhang et al, 2014;Liu et al, 2021) (Supplementary Table S3).…”
Section: Gwa-qtl Identifiedmentioning
confidence: 52%
See 2 more Smart Citations
“…The most commonly identified StHD QTL was qStHD8-2, which co-located with QTL previously identified in four different populations (Pan et al, 2012;Li et al, 2016;Murugaiyan et al, 2019). When the RMC QTL for grain-As were compared with previously reported As QTL determined in various biparental mapping or GWA populations (Zhang et al, 2008;Norton et al, 2012a;Norton et al, 2014;Zhang et al, 2014;Norton et al, 2019;Liu et al, 2021), nine of the 15 RMC grain-As GWA-QTL coincided with a previously reported grain-As locus (Table 4). Four of the 11 RMC QTL for P, six of 18 for S, one of 19 for Ca, and 2 of 9 for Cu were validated by known transporter genes or previous QTL studies (Zhang et al, 2014;Liu et al, 2021) (Supplementary Table S3).…”
Section: Gwa-qtl Identifiedmentioning
confidence: 52%
“…When the RMC QTL for grain-As were compared with previously reported As QTL determined in various biparental mapping or GWA populations (Zhang et al, 2008;Norton et al, 2012a;Norton et al, 2014;Zhang et al, 2014;Norton et al, 2019;Liu et al, 2021), nine of the 15 RMC grain-As GWA-QTL coincided with a previously reported grain-As locus (Table 4). Four of the 11 RMC QTL for P, six of 18 for S, one of 19 for Ca, and 2 of 9 for Cu were validated by known transporter genes or previous QTL studies (Zhang et al, 2014;Liu et al, 2021) (Supplementary Table S3). Because alternate alleles became very rare in the smaller subpopulations, the table presents the results based on the entire RMC panel when the QTL was significant there.…”
Section: Gwa-qtl Identifiedmentioning
confidence: 77%
See 1 more Smart Citation
“…This makes the application of latent phenotyping more challenging for basic biological questions than for prediction. Despite these challenges, latent phenotyping approaches have been used to successfully identify genetic loci linked with tomato fruit and leaves (Chitwood et al., 2012; Li, Frank, et al., 2018; Wang et al., 2019), rice grains (Iwata et al., 2015), the maize, rice, and soybean ionomes (Chu et al., 2016; Fikas et al., 2019; Liu et al., 2021), the Brassica defensive metabolome (D'Oria et al., 2021; Katz et al., 2021), oat seed fatty acid concentrations (Carlson et al., 2019), inflorescence development in maize and sorghum (Leiboff & Hake, 2019; Rice et al., 2020), carrot shoot and roots (Turner et al., 2018), response to drought in Setaria (Ubbens et al., 2020), and strawberry fruit shape (Nagamatsu et al., 2021). Some of these successful examples have relied on prior information from preceding univariate analyses to validate the loci discovered using latent phenotyping and to aid their interpretation of those newly discovered loci (Fikas et al., 2019; Katz et al., 2021; Ubbens et al., 2020).…”
Section: The Cave the Fire And The Shadows In Plant Phenotypingmentioning
confidence: 99%
“…The carryover effect of these shifts into the soil microbial populations is an ongoing area of research (Fernández-Baca et al, 2021b). Genetic approaches are also used to decrease root to shoot translocation of Cd (Ueno et al, 2009;Yan et al, 2019), and to identify genes associated with uptake of multiple essential elements in different growth conditions (Zhang et al, 2014;Liu et al, 2021), locations (Norton et al, 2014), and varieties (Pinson et al, 2015).…”
Section: Complementary Rice Breeding Research Effortsmentioning
confidence: 99%